Slovenščina na poklicni maturi - Hodak, Marjana (Jezik in slovstvo, 2012)
Since 2002, pupils in vocational upper secondary education have been required to pass a vocational matura examination that comprises a written and an oral part. The written part is external, with the exam materials and assessment instructions being prepared by the National Committee for the Vocational Matura for the subjects of Slovene and Slovene as a second language. The oral exam is carried out internally, and organised and prepared in terms of content by school teachers. The article presents a detailed analysis of the written exam, the degree of cognitive diffculty of tasks in the non-literary text analysis, and the success of the candidates in task solving.
Keywords: Slovene; slovenščina; neumetnostno besedilo; matura; poklicna matura; preverjanje